Occupational health risk among healthcare workers during COVID-19 pandemic: actions to limit the risk - Eman Casper (SpringerOpen, 2021)
Abstract The World Health Organization declared coronavirus infection 2019 (COVID-19) as a pandemic in March 2020. The infection with coronavirus started in Wuhan city, China, in December 2019. As of October 2020, the disease was reported in 235 countries. The coronavirus infection 2019 (COVID-19) is a disease with high morbidity and mortality. As of February 2021, the number of confirmed cases of COVID-19 globally is 102,942,987 and 2,232,233 deaths according to WHO report. This infection is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which is a ribonucleic acid (RNA) β-coronavirus. The infection is mainly transmitted through respiratory droplets. Healthcare workers (HCWs) play an essential role at the front lines, providing care for patients infected with this highly transmittable disease. They are exposed to very high occupational health risk as they frequently contact the infective persons. In order to limit the number of infected cases and deaths among healthcare workers, it is crucial to have better awareness, optimistic attitude, efficient PPE, and adequate health practices about COVID-19.